2008
DOI: 10.1189/jlb.1107768
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids induce an activated, anti-inflammatory monocyte subset in mice that resembles myeloid-derived suppressor cells

Abstract: Glucocorticoids (GC) are still the most widely used immunosuppressive agents in clinical medicine. Surprisingly, little is known about the mechanisms of GC action on monocytes, although these cells exert pro- and anti-inflammatory effects. We have shown recently that GC induce a specific monocyte phenotype with anti-inflammatory properties in humans. We now investigated whether this also applies for the murine system and how this subset would relate to recently defined murine subtypes. After treatment with dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
126
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 23 publications
13
126
0
1
Order By: Relevance
“…16 Here we confirm these findings and show that HLA-DR/DP/DQ loss in Dex-treated patients is independent of disease grade (Figure 6A). Consistent with the fact that the gene for CD163 is glucocorticoid-regulated, 18,22,29 we found that CD163 was expressed on a higher percentage of circulating CD14+ monocytes in Dex-treated low and high-grade glioma patients (Figure 6B). In contrast, we see no change in the frequency of the commonly used MDSC marker CD33 (Figure 6C) or the T cell suppressive marker PD-L1 (Figure 6D), indicating that Dex doesn’t universally suppress surface protein expression, but may have specific targets.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…16 Here we confirm these findings and show that HLA-DR/DP/DQ loss in Dex-treated patients is independent of disease grade (Figure 6A). Consistent with the fact that the gene for CD163 is glucocorticoid-regulated, 18,22,29 we found that CD163 was expressed on a higher percentage of circulating CD14+ monocytes in Dex-treated low and high-grade glioma patients (Figure 6B). In contrast, we see no change in the frequency of the commonly used MDSC marker CD33 (Figure 6C) or the T cell suppressive marker PD-L1 (Figure 6D), indicating that Dex doesn’t universally suppress surface protein expression, but may have specific targets.…”
Section: Resultssupporting
confidence: 84%
“…14 Although glucocorticoid signaling increases expression of CD163 on myeloid cells, 22,29 the effects on accumulation of CD163+ cells in tumor tissue are less well understood. Recent work suggests that variation in the expression of macrophage immune modulatory proteins is more critical to disease progression than macrophage accumulation within the tumor.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a genomic analysis of the CD163 promoter region revealed the presence of several binding sites for transcription factors in the 5Ј-flanking region (45), including three putative glucocorticoid receptor binding sites. In fact, monocytes that had been treated with glucocorticoids or derived from patients on glucocorticoid pulse therapy showed a strongly induced CD163 expression (12,15,46,47). Taking the collective findings into consideration, with the evidence that glucocorticoid also up-regulates AGP synthesis (20), glucocorticoids might not only regulate CD163 expression directly but also indirectly via enhancing AGP production.…”
Section: Discussionmentioning
confidence: 99%
“…The latter group are notable for their "deactivated" phenotype, migrating to sites of infection where they have an enhanced ability to clear debris and apoptotic cells by a non-phlogistic mechanism (Ren et al, 2001) which is, in turn, stimulated by glucocorticoids , thus actively contributing to the resolution of inflammation (Savill et al, 2002). Intriguingly, it has recently been reported that the anti-inflammatory monocytes induced by glucocorticoids resemble myeloid-derived suppressor cells, a finding with implications for tumour progression under conditions of glucocorticoid excess (Varga et al, 2008).…”
Section: The Key Playersmentioning
confidence: 99%
“…During inflammation, predominantly a response of the innate immune system, glucocorticoids restrain oedema, increase blood viscosity and alter leukocyte distribution/trafficking, haematopoietic differentiation programmes and gene transcription . Importantly, they also promote the resolution of inflammation by inducing an anti-inflammatory phenotype in differentiating monocytes (Ehrchen et al, 2007;Giles et al, 2001;Varga et al, 2008), promoting survival of anti-inflammatory macrophages (Mφ) during inflammation and increasing non-phlogistic phagocytosis of apoptotic neutrophils by Mφ (reviewed (Heasman et al, 2003;Yona and Gordon, 2007)). Endogenous glucocorticoid activity depends upon glucocorticoid output from the adrenal gland, under the control of the hypothalamic-pituitary-adrenal (HPA) axis and indeed, infection or trauma is a potent stimulus to the HPA axis (Sternberg, 2001).…”
mentioning
confidence: 99%